Almost home - Baskin, Nora Raleigh (Walker London, 2004)
Leah Baer misses her mum; she writes to her almost every day. About not liking school. About Dad and Gail. And now about Will. But there is something that Leah doesn't mention to her mum in her letters, or even admit to herself. And until she does, Leah can't move on